Performance Improvement of the AOA Estimation Algorithm Using the Newton Iteration - Lee, Joon-Ho; Cho, Sung-Woo (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a simple numerical method based on the Newton iteration for improving the accuracy of the Conventional beam forming algorithm, the Capon beam forming algorithm, and the MUSIC algorithm for AOA (Angle-of-Arrival) estimation is presented. Based on observation, the estimates of the AOA’s for a specific AOA algorithm can be obtained from the extrema of a cost function associated with the specific AOA algorithm employed. We derive explicit expressions of the iterations used for the recursive update of the estimates of the AOA’s for the conventional beam forming algorithm, the Capon beam forming algorithm, and the MUSIC algorithm. The formulation is only for the update of the azimuth angle, while the extension to the update of the elevation angle and the azimuth angle can be implemented by taking into account the dependence of the array manifold on the elevation angle as well as the azimuth angle. Note that, for estimation of the azimuth, both the UCA (uniform circular array) and the ULA (uniform linear array) can be employed, and that, for simultaneous estimation of the elevation and the azimuth angle, the UCA, not the ULA, should be adopted since ULA-based algorithm cannot uniquely estimate both the azimuth and the elevation due to the ambiguity pertinent to the ULA structure. We consider the array structure of the ULA and the UCA, but it is quite straightforward to extend the proposed scheme to an arbitrary array structure by simply modifying the array vector consistently with the specific array structure. Index Terms - AOA, accuracy improvement, conventional beam forming algorithm, Capon beam forming algorithm, MUSIC algorithm, Newton method, UCA, and ULA.